A first investigation on tricolor langur (Presbytis chrysomelas subsp. cruciger) exhibits significant terrestrial activity in their natural habitat - SUTOPO SUTOPO; NYOTO SANTOSO; ANI MARDIASTUTI; YENI ARYATI MULYANI (Society for Indonesian Biodiversity, 2024)
cruciger) exhibits significant terrestrial activity in their natural habitat. Biodiversitas 24: 3431-3440. Until now, it has only been reported that the tricolor langur (Presbytis chrysomelas subsp. cruciger Thomas 1892) is a semi-terrestrial primate, but there has never been any proof from their natural habitat that they actually engage in ground-level activities. This research aims to investigate terrestrial daily activity and the daily time budget for the tricolor langur. To determine the duration and type of their natural behaviors, observations using camera traps. This research was conducted from July 2022 to June 2023 in the lowland forest around the foot of Semujan Hill, which is part of the Danau Sentarum National Park Area, Kapuas Hulu District, West Kalimantan, Indonesia. The results of observations using camera traps showed that the one group langurs engaged in terrestrial activities for 5,830 seconds and arboreal activities in the tree canopy for 15,160 seconds. The percentage of total time recorded by the camera traps indicates that terrestrial activity accounts for only 34% of the total recorded time. The most dominant activities during both terrestrial and arboreal activities were eating and locomotion, with the rest being grooming, resting, and playing. The findings of this research contribute to our understanding of primate behavior, highlight effective methods for observing primates in their natural habitat, especially the Presbytis group and raise awareness among park managers and local communities. It is important that langurs are not disturbed during their terrestrial activities to ensure their continued presence and population growth in the study area.